ESP COURSE DESIGN: AN INTEGRATED APPROACH - Sitti Nurpahmi (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2016)
ESP course design has grown to become one of the most prominent areas of EFL teaching since the early 1960's. It is a phenomenon that grew out of a number of covering trends. Nowadays there are many courses are offered in ESP areas. There has been several approaches in designing course but each of them has weakness and strengthens. This article aims at finding new approaches in ESP course design that integrate all the needs that the course. It integrates three com-ponent of need analysis, PSA, TSA, and LSA, and integrated source of data-stake-holder, learner, teacher, and expert. Each of the steps of integrated approach in-tegrate all component needed.